Should income be taken for granted as a sole driver of welfare? Bayesian insight on the relevance of non-income drivers of welfare - Tomasz Piotr Wisniewski (International Journal of Management and Economics, 2018)
The paper consists of a discussion on the relevance of non-income drivers of welfare. This discussion is based on a subjective Bayesian reasoning, where welfare perceptions are subjectively rational decisions of individuals, who are, as author suggests, the ultimate decision-makers in respect of what welfare actually means for them. The objective of the paper is to investigate if income should be taken for granted as a sole driver of welfare. The conclusion is drawn from a methodological investigation of this question in a Bayesian concept of probability with a consideration for correlations among income and non-income drivers of welfare. It suggests that income should not be taken for granted as a sole driver of welfare since the non-income factors, which are not correlated with income, appear to be relevantly affecting individuals' perceptions of welfare with Bayesian probability of almost 65%. Thereby, the paper is a reaffirmation of a need for further research in the area of welfare measures that might constitute an alternative to income-dominated indicators. Its value emanates from unambiguous answer in favour of the relevance of non-income drivers across welfare perceptions, which, without Bayesian reasoning, could remain unsolved at the point of 50% odds for relevance (irrelevance).
Keywords: I 31; C 11; 650; welfare; non-income welfare; subjectivism of welfare; drivers of welfare; welfare perception; welfare measurement; Bayesian probability